Gaussian Process Regression Applied to VRLA Battery Voltage Prediction in Photovoltaic Off-Grid Systems - Sanz Gorrachategui, Iván; Bernal Ruiz, Carlos; Bono Nuez, Antonio; Pajovic, Milutin; Martínez Ruata, Gabriel (Jornada de Jóvenes Investigadores del I3A, 2018)
This study addresses the use of GPR techniques for VRLA battery voltage prediction purposes in PV off-grid systems. The goal is to know whether the system is able to endure a predictable power consumption pattern without running out of energy. Two approaches are considered: sample based prediction and pattern-based forecasting.